The Prevalence of Elder Abuse and its Association with Frailty in Elderly Patients at the Outpatient Department of a Super-Tertiary Care Hospital in Northern Thailand - Yanee Choksomngam; Terdsak Petrungjarern; Perapoln Ketkit; Pakpoom Boontak; Ratchanon Panya; Tinakon Wongpakaran; Nahathai Wongpakaran; Peerasak Lerttrakarnnon (Medicina, 2023)
Background and Objectives: The global population is undergoing rapid aging, resulting in an increase in geriatric syndromes and hidden health issues such as elder abuse. However, the prevalence of elder abuse varies across different settings. The objective of this study is to determine the prevalence and factors associated with elder abuse at the outpatient department of a super-tertiary care hospital in northern Thailand. Materials and Methods: This cross-sectional study involved 210 elderly patients who visited Maharaj Nakorn Chiang Mai Hospital between May and August 2022. The participants completed several assessments, including the Mini-Cog, Thai Geriatric Depression Scale-6, Core Symptom Index-15, FRAIL scale, Barthel Activities of Daily Living, Interview Guideline for Screening for Elder Abuse, and Diagnostic Criteria for Elder Abuse. Fisher’s exact test was used to examine the association between the factors and elder abuse. Results: The Screening for Elder Abuse yielded noteworthy results, with 15.7% of the elderly patients having experienced psychological abuse. However, only a smaller subset of study participants, comprising five individuals or 2.38%, met the diagnostic criteria for elder abuse. Furthermore, statistical analysis revealed no significant correlation between elder abuse and the other factors examined in the study. Conclusions: As a result, it is crucial for hospitals to consider preventive measures and implement routine screening protocols.